Currículo e o Ensino de Enfermagem em Cuidados Paliativos na Região Norte do Brasil - Santana, Euzamar de Araujo Silva (2019)
Introduction: The medicine advances enabled transformations in the body and increased life expectancy, but a certainty remains, the Death, still feared by many people, for representing "The End". The family structure has changed, and people affected by chronic diseases, with no therapeutic possibility of cure, have resorted to the care of health professionals, often unprepared to deal with the end of life. In this context, palliative care arises, with the purpose of promoting quality of life and relief of suffering, focused on the integral care of the person, considering the biopsychosocial and spiritual dimensions. The nurse, a member of the multidisciplinary team, needs to be able to assist the terminal patient, through palliative care, to do this, the educational institutions need to contemplate the theme in their curriculum grid. Objectives: Objectives: To verify how the process of death and dying and/or palliative care are being approached in the national curricular guidelines of degree nursing courses and in the curriculum of degree courses in nursing, from the public universities of the north region of Brazil. Methods: It consisted of two stages: the first step was the production of a literature review article about the theme, allowing the deepening of the subject, and a second stage was made a descriptive, exploratory, documental study with a qualitative approach, conducted between January 2018 and July 2019, in which the DCNsENF and the curriculum of the degree courses in public nursing in northern Brazil were evaluated, recognized and active in E-MEC. The universities that did not make the documentation available on the site were excluded and that it was not possible to contact them. For the search in the E-MEC, the variables were adopted: Degree course; Nursing course; In the seven states of the northern region of Brazil; Free Bachelor and bachelor’s degree with active status. The documentary analysis was considered: Objective of the course; Profile of the egress/professional; Competencies and skills of the nurse; Axes/modules/disciplines or related that contemplate the end of the life, death and dying process and/or palliative care. Results: Selected in the E-MEC 10 institutions, one inserted the discipline of palliative care and Thanatology (optative) in its curriculum; Five, approached in their pedagogical projects the process of , death and dying and/or palliative care, however, did not include in their curricular matrices specific discipline; While four were contemplative in their curriculum the principles of universality, fairness, comprehensiveness and humanization of care, converging with the principles of palliative care, however, did not address the process of end of the life, death and dying and/ or palliative care in your curriculum. Considerations: Evidence of a gap in the DCNsENF, concerning the approach of the theme, finitude process, death and dying and/or palliative care, reflected in the curricula of the forming institutions. The omission found suggests a review of the DCNsENF, in order to substantiate the readjustment of the curriculum of degree nursing courses. It is of paramount importance the inclusion of the discipline palliative care, as a mandatory component, in the DCNs and in the nursing PPCs of all the HEI in Brazil, in order to ensure the contemplation of the theme in the training of nurses.